The Mojing: origins and development of Mohist logic - Sun, Zhongyuan (Modern Chinese philosophy, 2024)
"This book, translated by Daniel Sarafinas, is the first and only English language translation of Sun Zhongyuan's research on Mohist logic. Sun investigates the historical contributions made to the research of logic in China, its modern value, its significance to the world, and how the form of logic developed in China is united with those from the rest of the world, focusing on Mohist (mojia) logic in particular as its core concern. Sun's work represents a high level of academic merit in the field of logic in China, embodying traditional Chinese culture, reflecting the frontiers of Chinese academia, effectively advocating for Chinese academia to engage with the rest of the world, deepening the academic conversation between China and the rest of the world, furthering the world's understanding of Chinese thought, and strengthening its influence and discursive power"--